Extrapolative projections of mortality: Towards a more consistent method part I: the central scenario - Dalkhat M. Ediev (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2008)
After a comparative study of the Lee-Carter forecasting method and looking into the direct extrapolation of mortality by age and sex, this paper advocates the use of the latter method. The method is, however, supplemented by additional procedures in order to improve its efficiency in the short run and preclude implausible mortality patterns in the long run. The short-run efficiency is improved by building the forecast on data from the most recent periods of age/sex-specific duration, when the mortality dynamics exhibit a steady trend. In the long run, the rates of the decline in mortality are assumed to converge to a plausible function of age and sex, which is derived from the data based on the assumption that it is a monotonic function of age. The framework proposed also provides a natural basis for developing multi-regional projection methods and also for introducing uncertainty into the projection.
Keywords: 300; Mortality forecasting; direct extrapolation; age-specific death rates; Lee-Carter method; Sterblichkeit; Bevölkerungsprognose; Prognoseverfahren; Theorie